(3CfhGQ GdJfRjd hCSQGQ GdJChjds - (3GdHjVGhj, CHh SYjO, CHh GdNjQ, fGUQ GdOjf, YHO Gddg Hf YeQ Hf eMeO Hf Ydj(B685(3g`s
(3ChdgG (B:s
[(3JaSjQ ShQI GdfSGA (B] (3jdhfgG hjMQRhfgG, heeG JQc HjGf dcd eY GdaUd HGdYGed Ch dcd ejJ LYdfG hQGKkG eeG JQc Ydi Cf ef UdI ehGdj dCfg aj eYfi GdhGQK s
(3BNQgG (B:s
[(3JaSjQ ShQI GdESQGA(B] : (3hGdbfWGQ Cda ChbjI heGFJG ChbjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 110s
(3eYLe GdeDdajf (B2 / 266s
(3cTa GdXfhf (B1 / 186s
(3TPQGJ GdPgH (B5 / 392s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs